Scientometric Introspect of Digital Citizenship in Scopus Database From 1999 to 2022 - Mousumi Saha; Aditi Roy; Saptarshi Ghosh (International Journal of Information Science and Management, 2024)
Literary warrants on 'Digital Citizenship' published since its inception are still countable. The search executed to identify the bibliometric literature on ‘Digital Citizenship’ retrieved a meager outcome. Therefore, the study was pivoted with the data retrieved from the SCOPUS database. By utilizing normalized data and citation analysis to evaluate the influence across the various groupings, it is possible to see an almost linear rise in 2021 on the topic. Statistical and visual modeling software tools (R-Biblioshiny, Bibliometrix) were used in the study. It examines what this means for how bibliometric methodologies are used and disseminated in various situations. The study by the authors addressed bibliometric analysis and categorization of articles as per Ribble and Choi. Moreover, the paper discussed three field Plots (Sources-Keywords-Authors) and the most relevant authors. Furthermore, the study tried to testify to the fitness of Bradford's Law, trending topics on the subject, co-occurrence network by keywords, topic growth over the year, and a thematic map of topics from 1999 to 2022. The results were quite impressive. out of a total of 377 articles on digital citizenship, a scattering of subjects with numerous overlapped concepts like digital literacy, digital competence, higher education, technology, digital divide, cyber-bullying, information literacy, digital citizenship education, privacy, secondary education, adolescents, digital education, empowerment, primary education, university students have been identified.